Kinetika Reaksi Deasetalisasi Sintesa Kitosan Dengan Pendekatan Shrinking Core Model (SCM) - Annisa Rahmat; Ahmad Fadli; Amun Amri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Chitosan is poly (2-amino-2-deoxy-β- (1-4) -D-glucopyranose) with molecular (C8H11NO4)n which produced from chitin of ebi waste through deacetylation process. Chitosan can be synthesized from ebi waste using chemical methods through deproteinasi, demineralization and deacetylation. Research procedure was begining with the size reduction of ebi waste into powder size. Then the powder was treated with NaOH 3.5% (deproteinasi), the ratio of deproteinasi 1:10 (w / v) for 2 hours and the stirring speed of 150 rpm. Deproteinasi product was treated with HCl 1 N (demineralization), the ratio of demineralization 1:15 (w / v) for 1 h and the stirring speed of 150 rpm. Demineralised product was reacted using 50% NaOH (deacetylation), the ratio of deacetylation 1:25 (w / v) at a speed of 100.150 stirring, and 200 rpm with a temperature of 120 ° C for 2 hours. Samples were taken every 10 minutes rise as much as 10 mL, washed until pH neutral and dried. Deacetylation degree of chitosan analyzed using acid-base titration method. By the range between in the stirring speed of 100-200 rpm it proved that the faster some mixing the bigger it is of deacetylation of chitosan is between 74,54%-83,14%. Reaction kinetics model suitable to describe the events that occur in the synthesis of chitosan was a model that was a layer 2 results (chitosan) to control.Keywords: deacetylation, reaction kinetics, chitosan, waste ebi, shrinking core model.